WHAT IS THE NEED FOR BUILDING PARTS? – A COMPARISON OF CITYGML, INSPIRE BUILDING AND A SWEDISH BUILDING STANDARD - H. Eriksson; H. Eriksson; L. Harrie; J. M. Paasch; J. M. Paasch (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2018)
The need for digital building information is increasing, both in the form of 3D city models (as geodata) and of more detailed building information models (BIM). BIM models are mainly used in the architecture, engineering and construction industry, but have recently become interesting also for municipalities. The overall aim of this paper is to study one way of dividing a building, namely the division of a building into building parts in both 3D city models and in BIM models. The study starts by an inventory of how building parts are defined in 3D city model standards (CityGML, the INSPIRE building specification and a Swedish national specification for buildings) and in BIM models (Industry Foundation Classes, IFC). The definition of building parts in these specifications are compared and evaluated. The paper also describes potential applications for the use of building parts, on what grounds a building could be divided into building parts, advantages and disadvantages of having building parts and what consequences it can have on the usage of the building information. One finding is that building parts is defined similar, but not identical in the studied geodata specifications and there are no requirements, only recommendations on how buildings should be divided into building parts. This can complicate the modelling, exchange and reuse of building information, and in a longer perspective, it would be desirable to have recommendations of how to define and use building parts in for example a national context.